2011
DOI: 10.1007/s11033-011-0878-z
|View full text |Cite
|
Sign up to set email alerts
|

XPA A23G polymorphism and lung cancer risk: a meta-analysis

Abstract: Case-control studies on the association between XPA A23G and lung cancer have provided either controversial or inconclusive results. To clarify the effect of XPA A23G on the risk of lung cancer, a meta-analysis of all case-control observational studies was performed. Pooled odds ratios (ORs) for various polymorphisms were estimated using random and fixed effects models. The Q-statistic was used to evaluate the homogeneity, and Egger and Begg tests were used to assess publication bias. For the homozygote GG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
2
4
0
2
Order By: Relevance
“…There was no evidence showing correlation between XPA A23G polymorphism and lung cancer in Caucasians, which was the same with the meta-analysis performed by Zou et al 6 The above results showed XPA significant ethnic differences, which was one of the major causes of heterogeneity between studies. Therefore, we cautiously thought that actually AG gene carrier had protective effect on lung cancer risk compared with AA gene carrier in allover, especially in Asians.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…There was no evidence showing correlation between XPA A23G polymorphism and lung cancer in Caucasians, which was the same with the meta-analysis performed by Zou et al 6 The above results showed XPA significant ethnic differences, which was one of the major causes of heterogeneity between studies. Therefore, we cautiously thought that actually AG gene carrier had protective effect on lung cancer risk compared with AA gene carrier in allover, especially in Asians.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, we cautiously thought that actually AG gene carrier had protective effect on lung cancer risk compared with AA gene carrier in allover, especially in Asians. There was no evidence showing correlation between XPA A23G polymorphism and lung cancer in Caucasians, which was the same with the meta-analysis performed by Zou et al 6 The above results showed XPA significant ethnic differences, which was one of the major causes of heterogeneity between studies. Evidence from several studies supports the role of DNA repair systems in monitoring and repairing carcinogeninduced DNA.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations